Risk stratification of patients with syncope in an accident and emergency department - Crane, S (BMJ Group, 2002)
Objectives: This study categorised syncopal patients, in a British accident and emergency (A&E) department, into three prognostic groups, using American College of Physicians (ACP) guidelines. The one year mortality of the three groups was studied to see if risk stratification using these guidelines is applicable to these patients and also whether admission improved outcome. Methods: The records of all syncopal patients presenting to the Leeds General Infirmary A&E department during an eight week period from 2 November 1998 were identified. The cohort was grouped according to ACP guidelines into those who had an absolute indication for admission (group 1), a probable indication for admission (group 2) and no indication for admission (group 3). The actual disposal was recorded and for each patient mortality data were retrieved from general practices or health authorities one year later. The three groups were compared. Results: Two hundred and ten records (1.7% of all new patients aged 16 years or above) were analysed. Forty per cent of the cohort were not assigned a diagnosis after their assessment in A&E. Forty seven (22%) were placed in ACP group 1, 63 (30%) in ACP group 2 and 100 (48%) in ACP group 3. Thirty six per cent of those in group 1 had died within a year, 14% of those in group 2 and none of those in group 3. In neither group 1 patients ("high risk") nor group 2 patients ("moderate risk") did admission to the hospital seem to influence outcome. However, three patients died within a week of their presentation, and two of them had been discharged from A&E. Conclusion: It is possible to stratify syncopal patients presenting acutely to A&E, according to prognosis, using ACP guidelines. Disposal decisions for these patients should be based on their apparent prognosis (as defined in the ACP guidelines) and not on the diagnosis, which is often difficult to make.